Kubios Threshold-Based Artefact Correction Affects Heart Rate Variability Parameters in Elite Athletes - Itaborahy, Alex; Freire, Raul; Hausen, Matheus (Journal of science in sport and exercise (Online), 2024)
Purpose Kubios is an intuitive software intended to provide heart rate variability (HRV) processing. It is widely used to assess athletes’ readiness for new training sessions and autonomic balance responses to the training programme. However, Kubios’ filtering levels’ effect on artefact correction for elite athletes is still unclear. This study aims to assess the impact of different Kubios threshold-based artefact correction levels on the HRV-derived parameters in male and female elite athletes. Methods One hundred and seventeen elite athletes (55 females) from 21 Olympic sports participated in this study. All participants underwent an HRV recording in the morning after 24 h of no intense exercise, caffeine, and alcohol consumption. The heart rate signals were acquired with the Polar V800 monitor, and time and frequency domain-derived variables were calculated with and without Kubios’ five levels of filtering. Results Kubios filtering levels significantly affected the HRV results in both time and frequency domains in female and male elite athletes. “Medium”, “Strong”, and “Very Strong” filtering resulted in an interpolation larger than 5% (above recommended by the software developers) in 3.4%, 28.2%, and 95% of the entire group data, respectively. Moreover, the “Very Strong” filter significantly lowered HRV variables and promoted mean values exceeding the 5% interpolation for females (33.35%) and males (38.17%). Conclusion The “Very Low” and “Low” threshold-based artefact correction levels were more suitable for processing HRV data from female and male elite athletes when Kubios was used.